Proposals for the nomenclature of salivarian trypanosomes and for the maintenance of reference collections (1978)
Studies on the characterization of salivarian trypanosomes are at present developing rapidly and difficulties in communication tend to arise because of different procedures in the different laboratories concerned. Terms can be divided into two classes, those that are purely operational and simply describe the laboratory history of the organism, and those that imply characterization. Of the Linnaean taxa, the section Salivaria and the four subgenera thereof, Duttonella, Nannomonas, Pycnomonas, and Trypanozoon, are useful at the present time but lower taxa are often unsatisfactorily defined. Characters such as the clinical course of infection, which have been used for subspeciation, are being found to correlate with such characters as isoenzyme patterns, antigenic make-up and DNA constitution. Serial passage of organisms has serious disadvantages and so reference collections are primarily of stabilates—cryopreserved suspensions of living organisms. Methods for the preparation of antigens, antisera, and isoenzymes are briefly noted. Conventions for the documentation of reference collections are proposed, in particular that the designation of materials should consist of two components, one signifying the primary isolation and the other the particular derived material used. The requirements for rapid information retrieval and global cataloguing of materials are considered.